1995
DOI: 10.1159/000188546
|View full text |Cite
|
Sign up to set email alerts
|

Mitosis and the Presence of Binucleate Cells among Glomerular Podocytes in Diseased Human Kidneys

Abstract: Podocytes are highly differentiated cells that appear to be postmitotic. However, it is unclear whether cell division or the proliferation of podocytes takes place in the setting of glomerular injury. In this study, we analyzed the presence of mitotic figures and of binucleate or multinucleate podocytes in diseased human kidneys by light and electron microscopy. Among the 164 cases analyzed, mitotic figures in podocytes were found in only one cell, in a case of focal and segmental glomerulosclerosis, and 6 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 7 publications
3
51
0
Order By: Relevance
“…Podocytes are an essential part of the glomerular filtration barrier but cannot regenerate themselves. 40,41 Loss of podocytes beyond a certain threshold is sufficient to trigger glomerulosclerosis. 42,43 We recently showed that late in renal development, a fraction of podocytes are recruited from cells on Bowman's capsule (presumptive PECs), 25 offering the perspective that this mechanism might still be preserved in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes are an essential part of the glomerular filtration barrier but cannot regenerate themselves. 40,41 Loss of podocytes beyond a certain threshold is sufficient to trigger glomerulosclerosis. 42,43 We recently showed that late in renal development, a fraction of podocytes are recruited from cells on Bowman's capsule (presumptive PECs), 25 offering the perspective that this mechanism might still be preserved in adults.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, Ki-67 positive cells were predominantly non-tagged cells, and the podocytes rarely expressed Ki-67, which indicates that podocytes can re-enter the cell cycle. 28,29 Nonetheless, this is insufficient to guarantee cell division (proliferation) even in tagged cells expressing Ki-67. Taken together, we conclude that the great majority of hyperplastic epithelial cells in this model of FSGS are of PEC origin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that p27 Kip1 stabilizes the cell cycle of these terminally differentiated cells [36]. Increased p27 Kip1 expression is cell-protective and reflects a cellular reaction to injury or stress in podocytes [34].…”
Section: Discussionmentioning
confidence: 99%